Cover Crop Management in Vineyards of the Lower Orange River Region, South Africa: 2. Effect on Plant Parasitic Nematodes - Addison, P.; Fourie, J.C. (South African Journal of Enology and Viticulture, 2016)
This study was conducted as part of a larger investigation into the effect of management practices on selected sown cover crops and the effects thereof on grapevine performance. The aim of this study was to determine the effect of these cover crops on plant parasitic nematode populations under natural field conditions. The trial site was in an own-rooted Sultanina vineyard situated in the Lower Orange River of the Northern Cape Province. Three management practices were applied selectively to ten cover crop species, with two control treatments consisting of weeds. Nematodes were monitored for a period of four years. ‘Saia’ oats were indicated as being poor hosts to both root-knot and root-lesion nematodes, while ‘Overberg’ oats showed poor host status against ring nematodes. ‘Midmar’ ryegrass and ‘Paraggio’ medic were also poor hosts for root-knot nematodes, while grazing vetch appeared to be a good host for root-knot nematodes. The most notable result from this study was the relatively high numbers of all three nematodes on the vine row, as opposed to the inter-row where cover crops were established. This indicates that vines were much better hosts for these nematodes than the cover crops. It is recommended that if more definite trends are to be observed, Brassica species, which have direct toxic/repellant effects on nematodes, should be tested.